green
  • green
integral (cos^3(6x))
Mathematics
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
cos^3(6x) = cos(6x) * cos^2(6x); cos^2(6x) = 1-sin^2(6x); therefore cos^3(6x) =cos(6x)(1-sin^2(6x)) = cos(6x) - cos(6x)*sin^2(6x) Now you use the linearity of the integral operator: \[intcos(6x)dx;let u =6x --> du/dx = 6, so dx = du/6, thus we have (1/6)\intcos(u) du = (1/6)sin(u) +c1...but remember that u = 6x, so our actual solution is (1/6)sin(6x) +c1]
anonymous
  • anonymous
now for the other part: int of cos(6x)*sin^2(6x)...another substitution-this time let u = sin(6x) that implies that du/dx = (1/6)cos(6x) and that dx = 6du/cos(6x)... so we now have: int of cos(6x)*u^2du/cos(6x)...(cos(6x) cancels out and we're left with:) int of u^2 du = (1/3)u^3 +c2 (remember u = sin(6x) so: (1/3)sin^3(6x) +c2... thus our total answer is this: (1/6)sin(6x) +c1 + (1/3)sin^3(6x) +c2 (let c1 +c2 = k since constant +constant =constant) then final solution: (1/6)sin(6x) + (1/3)sin^3(6x) + k

Looking for something else?

Not the answer you are looking for? Search for more explanations.